Motivasi Ibu dalam Pemberian ASI Eksklusif - I Nyoman Ribek (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2014)
The purpose of this study was to determine the maternal motivation in exclusive breastfeeding in the Community Health Center I of North Denpasar. The method used was a descriptive study with cross sectional approach. Sample was 38 mothers of infants aged 0-6 months I came to the health center with the North Denpasar purposive sampling technique. Data was collected using a questionnaire. The results showed a large majority of the 38 respondents mostly maternal motivation in exclusive breastfeeding is strong that is equal to 68 %.